ANALISIS TINGKAT KEPUASAN KONSUMEN MELALUI MANAJEMEN PELAYANAN PADA RESTORAN BEBEK SINJAY BANGKALAN - Zahroh, Anilatus; Arisinta, Octaviana; Ulum, Romiftahul (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
In today's economy, every business, whether it's a jasa or a non-jasa one, is working hard to help new or long-term customers. To that end, it is necessary to carry out modifications, improvements, and expansions in a variety of areas in order to improve the quality of a company's operations and achieve its goals, particularly in the food service industry. Restaurants require evaluation in order to enhance sales and meet the projected aim. This study aims to determine consumer satisfaction with the management of services provided by Sinjay Duck Restaurant. The method that researchers use in this study is qualitative descriptive, where this method is an overview in the field of the level of customer satisfaction through service management using in-depth interviews. The data used are primary data and secondary data. From the results of this research analysis, it can be concluded that in the restaurant business to develop a good service management then pay more attention to what is requested by consumers such as being on time, fast and responsive in service, and understanding complaints experienced by consumers so that employees can serve well and optimally.